Have fun L'hopitaling this one!

Calculus Level 4

lim x 0 ( 1 cos x ) 58 ln 116 ( 2 x + 3 2 cos x ) \large \lim_{x \to 0} \dfrac{(1-\cos x)^{58} }{\ln^{116}(2x + 3 - 2 \cos x) }

If the above limit equals L L , compute log 2 L \log_2 L .

Hint: The problem is not meant to be laborious actually.


The answer is -174.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Hobart Pao
Dec 17, 2017

As x 0 x \to 0 , 1 cos x 1 2 x 2 1 - \cos x \approx \dfrac{1}{2} x^2 and ln ( 1 + x ) x \ln(1+x) \approx x . This comes from each respective Taylor polynomial. We can apply these two formulas in this limit.

= lim x 0 1 2 58 x 116 ln 116 ( 2 x + 1 + 2 2 cos x ) = \displaystyle \lim_{x \to 0} \dfrac{\dfrac{1}{2^{58}}x^{116}}{\ln^{116}\left(2x + 1 + 2 - 2 \cos x \right) } = lim x 0 1 2 58 x 116 ln 116 ( 2 x + 1 + 2 ( 1 cos x ) ) = \displaystyle \lim_{x \to 0} \dfrac{\dfrac{1}{2^{58}}x^{116}}{\ln^{116}\left(2x + 1 + 2( 1- \cos x) \right) } = lim x 0 1 2 58 x 116 ln 116 ( 2 x + 1 + x 2 ) = \displaystyle \lim_{x \to 0} \dfrac{\dfrac{1}{2^{58}}x^{116}}{\ln^{116}(2x + 1 + x^2 ) } = lim x 0 1 2 58 x 116 ln 116 ( x + 1 ) 2 = \displaystyle \lim_{x \to 0} \dfrac{\dfrac{1}{2^{58}}x^{116}}{\ln^{116}( x+1)^2 } = lim x 0 1 2 58 x 116 2 ln 116 ( x + 1 ) = \displaystyle \lim_{x \to 0} \dfrac{\dfrac{1}{2^{58}}x^{116}}{2 \ln^{116}( x+1) }
= lim x 0 1 2 58 x 116 2 x 116 = \displaystyle \lim_{x \to 0} \dfrac{\dfrac{1}{2^{58}}x^{116}}{2 x^{116} }
= lim x 0 1 2 58 x 116 2 x 116 = \displaystyle \lim_{x \to 0} \dfrac{\dfrac{1}{2^{58}}x^{116}}{2 x^{116} }
L = 1 2 59 ; log 2 L = 59 L = \dfrac{1}{2^{59}}; \log_{2} L = \boxed{-59}


Your mistake lies in ln 116 ( x + 1 ) 2 2 ln 116 ( x + 1 ) \ln ^ { 116} ( x+1)^2 \neq 2 \ln ^{116} ( x+ 1) . The friendlier notation is to write the LHS as [ ln ( x + 1 ) 2 ] 116 [ \ln (x+1)^2 ] ^ { 116 } .

Calvin Lin Staff - 3 years, 5 months ago

lim x 0 ( 1 cos x ) 58 ln 116 ( 2 x + 3 2 cos x ) = ( lim x 0 1 cos x ln 2 ( 2 x + 3 2 cos x ) ) 58 = ( lim x 0 2 sin 2 ( x 2 ) ln 2 ( 2 x + 3 2 cos x ) ) 58 = ( 2 lim x 0 ( sin ( x 2 ) ln ( 2 x + 3 2 cos x ) ) 2 ) 58 = ( 2 lim x 0 ( 1 2 cos ( x 2 ) 2 + 2 sin x 2 x + 3 2 cos x ) 2 ) 58 = ( 2 ( 1 4 ) 2 ) 58 = ( 1 8 ) 58 = 2 174 \begin{aligned} \lim_{x \to 0} \dfrac{(1-\cos x)^{58}}{\ln^{116}(2x+3-2\cos x)} &= \left(\lim_{x \to 0} \dfrac{1-\cos x}{\ln^2(2x+3-2\cos x)}\right)^{58} \\ &= \left(\lim_{x \to 0} \dfrac{2\sin^2 \left(\frac{x}{2}\right)}{\ln^2(2x+3-2\cos x)}\right)^{58} \\ &= \left(2\lim_{x \to 0} \left( \dfrac{\sin \left(\frac{x}{2}\right)}{\ln(2x+3-2\cos x)} \right)^2 \right)^{58} \\ &= \left(2\lim_{x \to 0} \left( \dfrac{\dfrac{1}{2} \cos \left(\frac{x}{2}\right)}{\frac{2+2\sin x}{2x+3-2\cos x}} \right)^2 \right)^{58} \\ &= \left(2\left(\dfrac{1}{4}\right)^2\right)^{58}\\ &= \left(\dfrac{1}{8}\right)^{58}\\ &= 2^{\boxed{-174}} \end{aligned}

Chew-Seong Cheong
Dec 23, 2017

L = lim x 0 ( 1 cos x ) 58 ln 116 ( 2 x + 3 2 cos x ) = lim x 0 ( 1 cos x ln 2 ( 2 x + 3 2 cos x ) ) 58 A 0/0 case, L’H o ˆ pital’s rule applies. = lim x 0 ( sin x 2 ln ( 2 x + 3 2 cos x ) ( 2 + sin x ) 2 x + 3 2 cos x ) 58 Differentiate up and down w.r.t. x = lim x 0 ( sin x ( 2 x + 3 2 cos x ) 2 ln ( 2 x + 3 2 cos x ) ( 2 + sin x ) ) 58 A 0/0 case again. = lim x 0 ( cos x ( 2 x + 3 2 cos x ) + sin x ( 2 + 2 sin x ) 2 ( 2 + sin x ) 2 2 x + 3 2 cos x + 2 ln ( 2 x + 3 2 cos x ) cos x ) 58 Differentiate up and down w.r.t. x = ( 1 8 ) 58 = 2 174 \begin{aligned} L & = \lim_{x \to 0} \frac {(1-\cos x)^{58}}{\ln^{116}(2x+3-2\cos x)} \\ & = \lim_{x \to 0} \left(\frac {1-\cos x}{\ln^2(2x+3-2\cos x)}\right)^{58} & \small \color{#3D99F6} \text{A 0/0 case, L'Hôpital's rule applies.} \\ & = \lim_{x \to 0} \left(\frac {\sin x}{ \frac {2 \ln(2x+3-2\cos x)(2+\sin x)}{2x+3-2\cos x}}\right)^{58} & \small \color{#3D99F6} \text{Differentiate up and down w.r.t. }x \\ & = \lim_{x \to 0} \left(\frac {\sin x(2x+3-2\cos x)}{2 \ln(2x+3-2\cos x)(2+\sin x)}\right)^{58} & \small \color{#3D99F6} \text{A 0/0 case again.} \\ & = \lim_{x \to 0} \left(\frac {\cos x(2x+3-2\cos x)+\sin x(2+2\sin x)}{\frac {2 (2+\sin x)^2}{2x+3-2\cos x} + 2 \ln(2x+3-2\cos x)\cos x}\right)^{58} & \small \color{#3D99F6} \text{Differentiate up and down w.r.t. }x \\ & = \left(\frac 18\right)^{58} = 2^{-174} \end{aligned}

log 2 L = 174 \implies \log_2 L = \boxed{-174} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...